2019
DOI: 10.15252/embr.201847026
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint kinase 1 is essential for fetal and adult hematopoiesis

Abstract: Checkpoint kinase 1 (CHK1) is critical for S‐phase fidelity and preventing premature mitotic entry in the presence of DNA damage. Tumor cells have developed a strong dependence on CHK1 for survival, and hence, this kinase has developed into a promising drug target. Chk1 deficiency in mice results in blastocyst death due to G2/M checkpoint failure showing that it is an essential gene and may be difficult to target therapeutically. Here, we show that chemical inhibition of CHK1 kills murin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 64 publications
(84 reference statements)
3
20
0
Order By: Relevance
“…Unfortunately, we were unable to confirm this since Chek1 heterozygous mice was not available at the time when we found that a heterozygous kinase-dead expressing Chk1 mouse did not exhibit any aging-related defects in erythropoiesis. Nevertheless, recently Schuler et al also demonstrated that whereas conditional deletion of both alleles of Chek1 using a Vav-Cre driver impaired hematopoiesis, heterozygous deletion had no impact on hematopoiesis or erythropoiesis (36). These data and ours argue that Chk1 is not haploinsufficient for erythropoiesis.…”
Section: Discussionsupporting
confidence: 65%
“…Unfortunately, we were unable to confirm this since Chek1 heterozygous mice was not available at the time when we found that a heterozygous kinase-dead expressing Chk1 mouse did not exhibit any aging-related defects in erythropoiesis. Nevertheless, recently Schuler et al also demonstrated that whereas conditional deletion of both alleles of Chek1 using a Vav-Cre driver impaired hematopoiesis, heterozygous deletion had no impact on hematopoiesis or erythropoiesis (36). These data and ours argue that Chk1 is not haploinsufficient for erythropoiesis.…”
Section: Discussionsupporting
confidence: 65%
“…Our study provided evidence that there is an association between CXC chemokines and the NF-κB signaling pathway during BLCA tumorigenesis and development. Our results also suggested Src family tyrosine kinases (LCK and LYN), PKN1, PRKG1, and CHEK1 might be the targets of the differential CXC chemokines, which play important roles in cell growth, division, migration, and survival signaling pathways [66][67][68][69], and mediate the carcinogenesis of several tumors [70][71][72]. Therefore, these differentially expressed CXC chemokines might modulate BLCA development and progression dependent on the above-mentioned signaling pathways by regulating these kinases.…”
Section: Discussionmentioning
confidence: 52%
“…3). This may be relevant for the critical role Chk1 plays in maintaining self-renewal, safeguarding HSC pool integrity, and minimizing mutational burden (Schuler et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The fetal liver (FL) takes on a crucial role for rapid clonal expansion during development. Not surprisingly, HSC rely on intact cell cycle checkpoints and DNA repair pathways to minimize the potential mutational burden in a highly proliferative HSC pool (Beerman et al, 2014;Schuler et al, 2019).…”
Section: Introductionmentioning
confidence: 99%